2021
DOI: 10.1007/s11136-021-02903-4
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the patient experience in hepatocellular carcinoma: a qualitative patient interview study

Abstract: Purpose This study aimed to elucidate the patient experience of hepatocellular carcinoma (HCC) to guide patient-centered outcome measurement in drug development. Methods Patients with HCC participated in qualitative interviews to elicit disease-related signs/symptoms and impacts, using discussion guides developed from literature searches and discussions with oncologists. Interview participants rated the disturbance of their experiences (0–10 scale). A conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 26 publications
0
34
0
Order By: Relevance
“…The studies also linked symptom burden to functional impacts on patients' lives. Pain, fatigue and dizziness were cited as symptoms causing the most functional limitation (Kaiser et al, 2014 ; Kimbell et al, 2015 ; Patel et al, 2022 ). As a result, many patients were no longer able to do normal activities of daily living (Gill et al, 2018 ; Patel et al, 2022 ), had to quit their jobs (Fan & Eiser, 2012 ; Gill et al, 2018 ; Kimbell et al, 2015 ) and spent more time confined to bed (Kaiser et al, 2014 ; Patel et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies also linked symptom burden to functional impacts on patients' lives. Pain, fatigue and dizziness were cited as symptoms causing the most functional limitation (Kaiser et al, 2014 ; Kimbell et al, 2015 ; Patel et al, 2022 ). As a result, many patients were no longer able to do normal activities of daily living (Gill et al, 2018 ; Patel et al, 2022 ), had to quit their jobs (Fan & Eiser, 2012 ; Gill et al, 2018 ; Kimbell et al, 2015 ) and spent more time confined to bed (Kaiser et al, 2014 ; Patel et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Pain, fatigue and dizziness were cited as symptoms causing the most functional limitation (Kaiser et al, 2014 ; Kimbell et al, 2015 ; Patel et al, 2022 ). As a result, many patients were no longer able to do normal activities of daily living (Gill et al, 2018 ; Patel et al, 2022 ), had to quit their jobs (Fan & Eiser, 2012 ; Gill et al, 2018 ; Kimbell et al, 2015 ) and spent more time confined to bed (Kaiser et al, 2014 ; Patel et al, 2022 ). Conversely, when patients had better physical health, they fared better overall (Fan & Eiser, 2012 ; Kaiser et al, 2014 ; Patel et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Patel et al found in interviews with 25 patients with BCLC stages that the most prevalent and disturbing experiences were fatigue, frustration, fear, and depression. [ 38 ] Abdominal pain and skin complaints were common and disturbing for BCLC‐C patients.…”
Section: Resultsmentioning
confidence: 99%
“…Manual processing of HCC and BTC interview data sets has previously been reported. 48,54 Participant demographics and clinical characteristics for each data set are listed in the Appendix in the Supplemental Materials found at https://doi.org/10.1016/j. jval.2022.06.004.…”
Section: Data Setsmentioning
confidence: 99%
“…42 Previous interview-based studies in oncology using manual processing identified symptoms of importance to guide the development of standardized PROs that adequately assess outcomes. [43][44][45][46][47][48] Both within and outside of the field of oncology, studies have investigated the use of NLP to detect and analyze symptom information from freetext formats in electronic health records for capturing symptoms, classifying or characterizing disease, and studying adverse events and clinical outcomes. [49][50][51][52] Nevertheless, knowledge of NLP application to improve cancer-related symptoms and their impact on QoL from qualitative patient interview data is limited.…”
Section: Introductionmentioning
confidence: 99%